Distribution of Random Variable Represented by a Binary Fraction with Three Identically Distributed Redundant Digits - Makarchuk, O. P.; Pratsiovytyi, M. V.; Макарчук, О. П.; Працьовитий, М. В. (Institute of Mathematics, NAS of Ukraine, 2014)
We present the complete solution of the problem of pure Lebesgue type of the distribution of random variable χ represented by a binary fraction with three identically distributed redundant digits.